Deregulation of phenylalnine biosynthesis evolved with the emergence of vascular plants. - El-Azaz-Ciudad, Jorge; Cánovas-Ramos, Francisco Miguel; Barcelona, Belén; Ávila-Sáez, Concepción; De-la-Torre-Fazio, Fernando Nicolás (Oxford University Press, 2022)
Phenylalanine (Phe) is the precursor of essential secondary products in plants. Here we show that a key, rate-limiting step in Phe biosynthesis, which is catalyzed by arogenate dehydratase, experienced feedback de-regulation during evolution. Enzymes from microorganisms and type-I ADTs from plants are strongly feedback-inhibited by Phe, while type-II isoforms remain active at high levels of Phe. We have found that type-II ADTs are widespread across seed plants and their overproduction resulted in a dramatic accumulation of Phe in planta, reaching levels up to 40 times higher than those observed following the expression of type-I enzymes. Punctual changes in the allosteric binding site of Phe and adjacent region are responsible for the observed relaxed regulation. The phylogeny of plant ADTs evidences that the emergence of type-II isoforms with relaxed regulation occurred at some point in the transition between nonvascular plants and tracheophytes, enabling the massive production of Phe-derived compounds, primarily lignin, a hallmark of vascular plants.
Keywords: Fenilalanina; Plantas - Sistema vascular; Phenylalanine; Vascular; Deregulation